2021
DOI: 10.3389/fcimb.2021.633817
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Clone Transmission of Carbapenem-Resistant Acinetobacter baumannii in ICU Rooms

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) is a major cause of nosocomial infections and hospital outbreaks worldwide, remaining a critical clinical concern. Here we characterized and investigated the phylogenetic relationships of 105 CRAB isolates from an intensive care unit from one hospital in China collected over six years. All strains carried blaOXA-23, blaOXA-66 genes for carbapenem resistance, also had high resistance gene, virulence factor, and insertion sequence burdens. Whole-genome sequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
5
21
0
Order By: Relevance
“…The results are consistent with previous studies showing that bla OXA-23 is the most widely reported gene, while bla OXA66 is the most common OXA variant in A. baumanni i [ 9 , 24 , 50 ]. In A. baumannii , the augmented antibiotic resistance is largely attributed to the actions of MGEs and the activation of intrinsic resistance mechanisms, such as chromosomal β-lactamases, bla ADC , and efflux pump activity [ 3 , 14 , 52 ]. In addition, diverse MGEs were found in the Ab27-HEnv isolate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results are consistent with previous studies showing that bla OXA-23 is the most widely reported gene, while bla OXA66 is the most common OXA variant in A. baumanni i [ 9 , 24 , 50 ]. In A. baumannii , the augmented antibiotic resistance is largely attributed to the actions of MGEs and the activation of intrinsic resistance mechanisms, such as chromosomal β-lactamases, bla ADC , and efflux pump activity [ 3 , 14 , 52 ]. In addition, diverse MGEs were found in the Ab27-HEnv isolate.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that insertion sequences, such as IS 26 , IS Vsa3 , IS Aba24 , and IS Aba26 , and a composite transposon were retrieved in the A. baumannii genome. The AdeFGH RND efflux pumps were previously identified in isolates with carbapenem resistance [ 52 ]. According to other reports, these genetic structures could facilitate the spread of antibiotic resistance determinants among pathogens, potentially compromising the effectiveness of many antibiotic treatments, including those prescribed to patients [ 3 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations